A WRKY Transcription Factor Regulates Fe Translocation under Fe Deficiency . Issue 3 (19th May 2016) - Yan, Jing Ying; Li, Chun Xiao; Sun, Li; Ren, Jiang Yuan; Li, Gui Xin; Ding, Zhong Jie; Zheng, Shao Jian
Abstract : A WRKY transcription factor promotes root-to-shoot Fe translocation under Fe deficiency via direct regulation of a vacuolar Fe transporter gene in Arabidopsis. Abstract: Iron (Fe) deficiency affects plant growth and development, leading to reduction of crop yields and quality. Although the regulation of Fe uptake under Fe deficiency has been well studied in the past decade, the regulatory mechanism of Fe translocation inside the plants remains unknown. Here, we show that a WRKY transcription factor WRKY46 is involved in response to Fe deficiency. Lack of WRKY46 ( wrky46-1 and wrky46-2 loss-of-function mutants) significantly affects Fe translocation from root to shoot and thus causes obvious chlorosis on the new leaves under Fe deficiency. Gene expression analysis reveals that expression of a nodulin-like gene ( VACUOLAR IRON TRANSPORTER1-LIKE1 [ VITL1 ]) is dramatically increased in wrky46-1 mutant. VITL1 expression is inhibited by Fe deficiency, while the expression of WRKY46 is induced in the root stele. Moreover, down-regulation of VITL1 expression can restore the chlorosis phenotype on wrky46-1 under Fe deficiency. Further yeast one-hybrid and chromatin immunoprecipitation experiments indicate that WRKY46 is capable of binding to the specific W-boxes present in the VITL1 promoter. In summary, our results demonstrate that WRKY46 plays an important role in the control of root-to-shoot Fe translocation under Fe deficiency condition via direct regulation of VITL1 transcript levels.